Direct numerical simulation of transitional pulsatile stenotic flow using Lattice Boltzmann Method - Jain,Kartik (PeerJ PrePrints, 2015)
In the present work, I perform direct numerical simulations of pulsatile flow through a 75% eccentric stenosis using the Lattice Boltzmann Method. The stenosis was studied by Varghese et al. (2007b) in a benchmark computation and the goal of this work is to validate the LBM solver Musubi for transitional flows in anatomically realistic geometries. Whereas most of the study reproduces and compares simulation results from Musubi against the benchmark, the latter part quantifies the Kolmogorov micro-scales and discusses the role of space and time resolutions for the simulation of a transitional flow. The LBM results show an excellent agreement with the previously published results thereby increasing confidence on our Musubi solver for the simulation of transitional flows. The aim of this study is not to compare the computational efficiency of the code or the method but only the physics of the flow.
Keywords: Stenosis; transitional flow; lattice Boltzmann Method; Kolmogorov microscales